Clinical management of tinnitus - Timurkaynak, Yasemin; Cobanoglu, H.Bengu; Imamoglu, Mehmet (Annals of Medical Research, 2021)
Aim: Tinnitus is defined as the perception of sound or sounds without any external audible source. Unknown ethiopathological mechanisms with lack of standardized protocol in symptom evaluation, causes difficulties in clinical management. Therefore, we aimed to evaluate the efficacy of magnesium, misoprostol and lidocaine treatments in patients with tinnitus.Material and Methods: The 58 tinnitus cases, were evaluated retrospectively. A total number of 40 patients who were able to comply with the scheduled therapy were received two staged therapy. As first line therapy, 20 patients with sensorineural hearing loss and acoustic trauma history were received oral magnesium, while remaining 20 cases without hearing loss were received oral misoprostol. Tinnitus handicap inventory (THI) was applied to all patients before and one month after the therapy. As second line therapy, 1.5mg/kg intravenous lidocaine was administered to the patients who had ineffective treatment results according to the THI.Results: The 40 patients included in this study were 10 female (25%), and 30 male (75%) and the mean age of all patients was 41,47 years. In both magnesium and misoprostol group, the mean scores of post-treatment THI were significantly lower than pre-treatment THI scores (p-values=0,001 and 0,007, respectively). No statistically significant difference was found between pre - and post treatment scores of the THI in lidocaine group.Conclusion: In present study, it was demonstrated that magnesium treatment is effective on tinnitus cases with acoustic trauma and misoprostol is effective on normal hearing tinnitus group, whereas intravenous lidocaine treatment was not found to be effective in tinnitus.
Keywords: Lidocaine; magnesium; misoprostol; tinnitus; tinnitus handicap inventory; tinnitus management